ポーラー パトロール キキュウ PPB II. カンソク ケイカク - 小玉, 正弘; コダマ, マサヒロ; 福西, 浩; フクニシ, ヒロシ; Kodama, Masahiro; Fukunishi, Hiroshi (1984)
P(論文) 南極大陸上の成層圏高度(-30km)を任意の緯度線に沿って一周するポーラー・パトロール気球(PPB : Polar Patrol Balloon)を利用して, どんな観測が可能か, あるいは望ましいかを検討する。超高層物理, 気象, 雪氷など広い分野にわたって, 人工衛星, ロケットなど他の飛翔体では不可能もしくは非効率的だが, PPBでは効率的に実現可能な観測計画について述べる。 As described in Part I, from a feasibility study of the Polar Patrol Balloon (PPB) which circles along a selected geographic latitude over Antarctica, it has been concluded that the PPB will be developed in the near future. The application of the PPB system is discussed in this paper. By the PPB experiment many subjects of upper atmosphere physics, meteorology, glaciology, cosmic ray physics and logistics will be solved, the subjects which have not been solved by technique of spacecraft and sounding rocket. departmental bulletin paper